URINARY BLADDER RELAXANT EFFECT OF ARTEMISIA VULGARIS AND ASPALATHUS LINEARIS - Arif-ullah Khan; A. H. Gilani (Journal of Animal and Plant Sciences, 2015)
In isolated rabbit urinary bladder preparations, Artemisia vulgaris (Av.Cr) crude extract inhibited the contractions produced by carbachol (CCh, 1 µM) and high K+ (80 mM) in a  concentration-dependent (0.03-10 mg/mL) manners. The crude extract of Aspalathus linaeris (Al. Cr) relaxed the contractions produced by low K+ (25 mM) at concentration range of 0.3-1.0 mg/mL, having moderate inhibitory effect on contractions produced by K+ (80 mM). Contractions induced by low K+ were partially antagonized by glibenclamide (3 µM). These results indicate that urinary bladder relaxation produced by Artemisia vulgaris extract is mediated via dual, anticholinergic and Ca++ antagonist mechanisms, while that of Aspalathus linaris via dominant KATP channel opening and weak Ca++ channel blockade pathways. Thus the present study reveals the Artemisia vulgaris and Aspslathus linaeris medicinal usefulness in hyperactive bladder disorders
Keywords: Artemisia vulgaris; Aspalathus linaris; urinary bladder relaxation